2003
DOI: 10.1021/jf020691d
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant Activity of Some Pentacyclic Triterpene Acids and Their Fatty Acid Ester Analogues

Abstract: The 3-O-fatty acid ester derivatives (C(12)-C(18)) of two pentacyclic triterpenic acids, ursolic acid and oleanolic acid, were synthesized under mild esterification conditions in excellent yields (80-85%) and screened for their antifeedant activity, together with the parent acids, against the agricultural pest tobacco caterpillar larvae (Spodoptera litura F) in a no-choice laboratory study. The Urs-12-ene-28-carboxy-3beta-octadecanoate and olean-12-ene-28-carboxy-3beta-hexadecanoate were found to exhibit excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 13 publications
(27 reference statements)
1
38
0
1
Order By: Relevance
“…The hexane and MeOH extracts of stem bark and leaves of A. illustre were subjected to a classical chromatographic methods to yield the a new oleanane-type triterpene, olean-12-ene-11a-methoxy-3β-acetate (10), in addition to known, β-amyrin (3), 4 lupeol (4), 4 β-amyrin acetate (5), 4 lupeol acetate (6), 4 olean-12-ene-28-hydroxy-3β-tetradecanoate (7), 4 olean-12-ene-28-carboxy-3β-hexadecanoate (8), 5,6 ursolic acid (9), 4 β-yoimbine (1) The oxidation at CH-11 of 10 is adequate to introduce significant modification in fragmentation of this pentacyclic triterpene containing double bond between the carbon atoms CH-12 e C-13 in the mass spectrometer, revealing the absence of peaks produce by reaction Retro-DielsAlder (RDA), as observed in other triterpenes with such characteristics. 13,14 Confirmation of structure 10 was done by comparison with authentic sample of derivative monoacetate of triterpene 11-a-methoxy-β-amyrin isolated from Myroxylon balsamum (Fabaceae).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hexane and MeOH extracts of stem bark and leaves of A. illustre were subjected to a classical chromatographic methods to yield the a new oleanane-type triterpene, olean-12-ene-11a-methoxy-3β-acetate (10), in addition to known, β-amyrin (3), 4 lupeol (4), 4 β-amyrin acetate (5), 4 lupeol acetate (6), 4 olean-12-ene-28-hydroxy-3β-tetradecanoate (7), 4 olean-12-ene-28-carboxy-3β-hexadecanoate (8), 5,6 ursolic acid (9), 4 β-yoimbine (1) The oxidation at CH-11 of 10 is adequate to introduce significant modification in fragmentation of this pentacyclic triterpene containing double bond between the carbon atoms CH-12 e C-13 in the mass spectrometer, revealing the absence of peaks produce by reaction Retro-DielsAlder (RDA), as observed in other triterpenes with such characteristics. 13,14 Confirmation of structure 10 was done by comparison with authentic sample of derivative monoacetate of triterpene 11-a-methoxy-β-amyrin isolated from Myroxylon balsamum (Fabaceae).…”
Section: Resultsmentioning
confidence: 99%
“…A partir de Aspidosperma illustre, foi obtido como produto natural um novo triterpeno da série oleanano, o olean-12-en-11a-metóxi-3β-acetato (10), além dos triterpenos β-amyrina (3), lupeol (4), acetato de β-amyrina (5), acetato de lupeol (6), olean-12-en-28-hidróxi-3β-tetradecanoato (7), olean-12-en-28-carboxi-3β-hexadecanoato (8), ácido ursólico (9) e dois alcalóides indólicos monoterpênicos, β-ioimbina (1) e 1,2-desidroaspidospermidina (2). As substâncias isoladas foram identificadas através de métodos espectroscópicos, principalmente uni (RMN 1 H, 13 C, APT) e bidimensionais ( A new natural product oleanane-type triterpene, olean-12-ene-11a-methoxy-3β-acetate (10) was isolated from Aspidosperma illustre, together with β-amyrin (3), lupeol (4), β-amyrin acetate (5), lupeol acetate (6), olean-12-ene-28-hydroxy-3β-tetradecanoate (7), olean-12-ene-28-carboxy-3β-hexadecanoate (8), ursolic acid (9) triterpenes, and two monoterpenic indole alkaloids, β-yoimbine (1) and 1,2-dehydroaspidospermidine (2).…”
unclassified
“…It also showed strong antimolting activity against the last of these. Oleanolic acid (83) had some antifeedant activity against Spodoptera litura (Mallavadhani et al, 2003), and 3-acetoxy-oleanolic acid (84) showed antifeedant activity against Leptinotarsa decemlineata (the Colorado potato beetle) (Hua et al, 1991). (Fig.…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…The Urs-12-ene-28-carboxy-3β-octadecanoate and olean-12-ene-28-carboxy-3β-hexadecanoate were found to exhibit exceptionally potent antifeedant activities at 50 µg/cm 2 concentration (Scheme 13). 334 9.10.Anti-AIDS agents. Anti-HIV activity of ursolic acid and structurally related triterpenoids Oxidation of ursolic acid (1) yielded a 3-oxo-derivative (89), which was more toxic against uninfected H9 cells than its parent compound, but inhibited HIV-1 replication, with an improved EC 50 value of 0.11 g/mL.…”
Section: 9antifeedant Activity Of Some Triterpene Acids and Their mentioning
confidence: 99%